Interest Rate Pass-Through in Three EU Candidate Countries: The Case of Albania, North Macedonia and Serbia - Velickovski, Igor; Mamuchevska, Daniela (Macrothink Insitute, 2019)
The objective of the paper is to assess the interest rate pass-through in three EU candidate countries that is Albania, North Macedonia and Serbia. We rely on an error-correction model using monthly data over the period 2005-2019. Results suggest a complete interest rate pass-through in Albania, albeit it has been weakened during the economic and financial crisis. The relatively fast speed of adjustment indicates an effective interest rate transmission channel. In the Macedonian case, the changes of the monetary policy rate are transmitted completely to the bank lending rate, but not to the bank borrowing rate. The transmission via the money market rate has improved after the global economic and financial turmoil. In the case of Serbia, the results also suggest complete interest rate pass-through indicating that the monetary policy rate changes are transmitted into retail rates offered by the banks to savers and borrowers in the long run. Nevertheless, the speed of adjustment is relatively slow. In general, the estimated speed and extent of the response of money market interest rate and bank retail interest rates to changes in the monetary policy rate gives an indication of effective interest rate transmission channel in the case of Albania and Serbia. On the other hand, it is moderately effective in the case of North Macedonia given that the central bank rate changes affect mainly bank lending rate but not borrowing rate.
Keywords: Interest rate pass-through, Error-correction model, Central bank, Banks